2023
DOI: 10.1001/jamanetworkopen.2023.12425
|View full text |Cite
|
Sign up to set email alerts
|

Structural Racism and Long-term Disparities in Youth Exposure to Firearm Violence

Abstract: Young people's exposure to firearm violence in US cities has surged during the COVID-19 pandemic. 1,2 This study by Lanfear and colleagues 3 examines how long-term changes in firearm violence have influenced exposure across multiple birth cohorts in Chicago, Illinois. Comparing 4 cohorts from the Project on Human Development in Chicago Neighborhoods (PHDCN), Lanfear et al 3 find that any benefits younger cohorts might have from declines in citywide violence from 1994 to 2014 were erased by subsequent violence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The authors further found that Black and Hispanic respondents experienced higher rates of shootings near their residences compared to White participants. Combined, these studies and our results point to the pernicious effects that structural racism, in the form of ethnic/racial and socioeconomic segregation that concentrates violence in certain neighborhoods, has on urban youth (Jay, 2023).…”
Section: Latent Classsupporting
confidence: 70%
See 2 more Smart Citations
“…The authors further found that Black and Hispanic respondents experienced higher rates of shootings near their residences compared to White participants. Combined, these studies and our results point to the pernicious effects that structural racism, in the form of ethnic/racial and socioeconomic segregation that concentrates violence in certain neighborhoods, has on urban youth (Jay, 2023).…”
Section: Latent Classsupporting
confidence: 70%
“…Results from the LCA highlight the need to better understand how factors across more distal systems influence youth's exposure to violence (Bronfenbrenner & Morris, 2006;Cicchetti & Lynch, 1993;Jay, 2023;Overstreet & Mazza, 2003). While theoretical models describing macrosystem relations involved in youth violence exposure are not new, less research has focused on the role of exosystemic factors.…”
Section: Latent Classmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there are also charges including murder and serious gun offenses that automatically receive a no-release recommendation, preventing pretrial release and potentially contributing to racial inequities in pretrial detention. New Jersey and other localities are considering revisions and updates to their risk assessment tools, and the impacts of these policy reforms should also be evaluated for their consequences for racial justice and community health equity …”
Section: Discussionmentioning
confidence: 99%
“…New Jersey and other localities are considering revisions and updates to their risk assessment tools, and the impacts of these policy reforms should also be evaluated for their consequences for racial justice and community health equity. 44 , 45 …”
Section: Discussionmentioning
confidence: 99%